Teachers' Strategies in Combating Diseases in Preschools' Environments - Emmanuel Obeng-Gyasi; Melissa A. Weinstein; Jessica R. Hauser; Cecilia S. Obeng (MDPI AG, 2018)
Scholarship on child health indicates that the early years of life are vital for all aspects of health and development. In particular, a solid health foundation predicts good life outcomes; therefore, systematic strategies for combating diseases are needed to ensure optimal health of young children in early care environments. This study examined strategies used by 48 preschool teachers from 10 pre-schools in the US Midwest in order to combat diseases. The following results emerged: Participants noted that children should not attend childcare if they are vomiting, have a fever or have diarrhea. They should be symptom-free for at least one day before returning to school. It is recommended that children be sent home if they have any disease deemed to have adverse effects on their health during the school day. Participants noted further that children must not share hats in their childcare environments to avoid transfer of head lice. Since no strategies were mentioned to help children cope with emotional distress and illness, it is recommended that teachers develop strategies that will address emotional childhood diseases in order to help all children.